Remediation of contaminated soils by biotechnology with nanomaterials: bio-behavior, applications, and perspectives. (3rd April 2018) - Gong, Xiaomin; Huang, Danlian; Liu, Yunguo; Peng, Zhiwei; Zeng, Guangming; Xu, Piao; Cheng, Min; Wang, Rongzhong; Wan, Jia
Abstract: Soil contamination caused by heavy metals and organic pollutants has drawn world-wide concern. Biotechnology has been applied for many years to the decontamination of soils polluted with organic and inorganic contaminants, and novel nanomaterials (NMs) has attracted much concern due to their high capacity for the removal/stabilization/degradation of pollutants. Recently, developing advanced biotechnology with NMs for the remediation of contaminated soils has become a hot research topic. Some researchers found that bioremediation efficiency of contaminated soils was enhanced by the addition of NMs, while others demonstrated that the toxicity of NMs to the organism negatively influenced the repair capacity of polluted soils. This paper reviews the application of biotechnology and NMs in soil remediation, and further provides a critical view of the effects of NMs on the phytoremediation and micro-remediation of contaminated soils. This review also discusses the future research needs for the combined application of biotechnology and NMs in soil remediation.